Socio-cultural and Economic Determinants of Delayed Reporting of Breast Cancer Among Ghanaian Women: A Qualitative Study - Merri Iddrisu; Edward Yalin; Lydia Aziato; Emma Kwegyir-Afful; Katri Vehvilainen₋Julkunen (Nursing and Health Sciences Journal (NHSJ), 2023)
Delayed reporting of breast cancer continues to increase in African countries, including Ghana, which is attributable to socio-cultural and economic factors. However, there is a paucity of data on socio-cultural and economic determinants of delayed reporting of breast cancer in Ghana. This study aimed to explore the socio‐cultural and economic determinants of delayed reporting of breast cancer among Ghanaian women. The study adopted an exploratory descriptive qualitative design with purposive sampling to recruit 17 women with breast cancer from the Tamale Teaching Hospital, Ghana. Data were collected through in-depth interviews. Analysis: Data analysis was done using the thematic analysis approach. Delayed reporting was due to inaccurate information, the influence of social networks, cultural misconceptions, belief in alternative treatment, high cost of treatment, and extreme poverty. A combination of socio‐cultural and economic factors influences the delay in reporting breast cancer in Ghana. Culturally appropriate and adequate health information and education, integration of alternative treatment into the formal healthcare system in Ghana, and financial support from the government are needed to promote early reporting for treatment.